Permodelan ombak-angin menggunakan spektra Jonswap - Othman A. Karim (1991)
Wave forecasts and hindcasts are almost universally derived from wind field. Numerous wind-wave models have been developed in recent years. 7his paper reports the analysis of wind-wave model incorporating the formulation based on 'JONSWAP' relationships for wave spectra, resulting from a given wind speed and wave fetch. The theories that apply to wind-wave model are described along with the statistical analysis between the hindcasted values and the measured data available. From the analysis, it appeared that JONSWAP model produces a good degree of correlation, ranging from 80 to 90 percent. However, further validification tests have to be conducted on the model before overall verification of the applicability of the model is complete